Academic tutoring during COVID-19: Higher education students’ perspectives - Ponce, Salvador; Martínez, Yessica; Ruelas, Paul Yitzen; Toledo, David Guadalupe (Education Policy Analysis Archives, 2022)
The tutor’s role, as well as that of many others in the educational sphere, was affected by the current contingency product of COVID-19. As a result, the development of different strategies to identify the way this type of services unfolds was deemed essential for its own improvement. This article documents the results of a research exercise. The goal of this exercise was to identify, from the eyes of the students of a public state university in Mexico the way tutors carried out their duties during the health emergency. Results show a set of categories associated with satisfaction and dissatisfaction from the students’ comments. It is noted that most of their opinions are satisfactory. Conclusions show that whether from a satisfaction or dissatisfaction perspective, there are three elements commonly valued by students: communication, academic support and mentoring, and their tutors’ attitudes. Attention is drawn to the importance of also exploring studies from tutor’s perspectives in order to complement and look further into understanding tutoring’s development during this contingency.